Functional characterization of the citrus canker susceptibility gene CsLOB1. (30th March 2018) - Duan, Shuo; Jia, Hongge; Pang, Zhiqian; Teper, Doron; White, Frank; Jones, Jeffrey; Zhou, Changyong; Wang, Nian
Summary: Xanthomonas citri ssp . citri (Xcc) is an important plant‐pathogenic bacterium that causes citrus canker disease worldwide. PthA, a transcriptional activator‐like (TAL) effector, directs the expression of the canker susceptibility gene CsLOB1 . Here, we report our recent progress in the functional characterization of CsLOB1. Subcellular localization analysis of CsLOB1 protein in citrus protoplast revealed that CsLOB1 is primarily localized in the nucleus. We showed that CsLOB1 expression driven by dexamethasone (DEX) in CsLOB1‐GR transgenic plants is associated with pustule formation following treatment with DEX. Pustule formation was not observed in DEX‐treated wild‐type plants and in non‐treated CsLOB1‐GR transgenic plants. Water soaking is typically associated with symptoms of citrus canker. Weaker water soaking was observed with pustule formation in CsLOB1‐GR transgenic plants following DEX treatment. When CsLOB1‐GR‐ transgenic Duncan grapefruit leaves were inoculated with Xcc306ΔpthA4 and treated with DEX, typical canker symptoms, including hypertrophy, hyperplasia and water soaking symptoms, were observed on DEX‐treated transgenic plant leaves, but not on mock‐treated plants. Twelve citrus genes that are induced by PthA4 are also stimulated by the DEX‐induced expression of CsLOB1. As CsLOB1 acts as a transcriptional factor, we identified putative targets of CsLOB1 via bioinformatic and electrophoretic mobility shift assays. Cs2g20600, which encodes a zinc finger C3HC4‐type RING finger protein, has been identified to be a direct target of CsLOB1. This study advances our understanding of the function of CsLOB1 and the molecular mechanism of how Xcc causes canker symptoms via CsLOB1.